A study of Belarusian women’s perceptions of safety and its relationships with victimization and social gender - I. V. Golyakova; V. А. Karpiyevich (Вестник университета, 2024)
The differences between Belarusian women’s perceptions of safety, as well as the links between these perceptions with victimization and social gender have been analyzed. The purpose of the study is to identify the peculiarities of women’s perceptions of safety, considering its relationship with victimization and social gender. Methods used: analysis and synthesis, method of interview and psychological testing, results processing and generalization, tabular, etc. The psychological safety perceptions assessment has been studied with the help of N.E. Kharlamenkova’s psychological safety questionnaire and victimization with the help of V.P. Sheinov’s methodology, to determine gender-role peculiarities the masculinity-femininity scale from the Freiburg Personality Inventory (FPI) was used. The sample included 590 women aged 18 to 60 years old. Differences in perceptions of psychological safety among women of different age groups have been revealed. It has been shown that for women security is associated with such concepts as peace in their country, reliability, health, and control of the situation. Adult women also associate safety with compliance with norms and rules, possession of information, and a reliable companion. For young girls, security is also associated with a sense of comfort, trust, and lack of anxiety. Perceptions of safety differ between feminine and masculine women. It has been shown that feminine-type women associate safety with their qualities and abilities, and masculine-type women associate it with the attitude to solving personal safety problems with the help of psychological strength and orientation to independence.